Implementasi Metode Role Playing Dalam Pembelajaran Sejarah - Dokolamo, Hamid (Program Studi Pendidikan Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pattimura, 2022)
In the learning process for history subjects, conventional approaches still dominate, remaining teacher-centred. History lessons often appear to simply involve the teacher transferring knowledge to students through lectures based on textbook material. Students are rarely encouraged to interact and collaborate with their peers or the teacher. History teachers tend to focus only on explaining historical facts such as chronological dates, names of figures, places, and events without making efforts to impart meaning to these historical occurrences. Students perceive memorizing historical facts as a heavy burden, viewing the material as too extensive and lacking practical value. The role-playing method is a teaching and learning process categorized under simulation methods. A simulation is a teaching approach that involves mimicking behaviours in a controlled setting. In history education, the role-playing method can be utilized to engage students in acting out the roles of figures involved in historical events. The implementation of the role-playing method in history education is expected to enhance students' process skills and learning outcomes. The learning process through role-playing can provide students with examples of human behaviour that serve as tools for understanding life. Additionally, this method is anticipated to improve students' process skills and academic performance.